Assessment of Grounding System to Reduce Potential Electrical Disturbances at Haji Regional General Hospital, East Java Province - Widagdo, Reza Sarwo; Budiono, Gatut; Tauladan, Imam Suri; Tasmono, Hadi; Nababan, Wendi Antonius S (Perkumpulan Kualitama Edukatika Indonesia, 2024)
The grounding system in the Hospital is used to overcome when there is a touch voltage and step voltage on the transformer and also other equipment installed on the transformer. The process carried out in this study was carried out by measuring the grounding and processing the data used to determine the size and smallness of the touch voltage and Step voltage. The results of the calculation of the grounding resistance in the hospital obtained a value of 5,056 ? which can cause a touch voltage with a value of 1014 V. The step voltage in humans weighing 50 Kg produces a value of 962,8 V and the step voltage for humans weighing 70 Kg produces a value of 1299 Volts. With the results of the values ??obtained, that the value has been in accordance with the standard of Step voltage based on IEEE 80-2013 with a value of 3,140 V with a duration of disturbance of 0,5 seconds.